2017
DOI: 10.1080/21645515.2017.1358325
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for emerging infectious diseases: Lessons from MERS coronavirus and Zika virus

Abstract: The past decade and a half has been characterized by numerous emerging infectious diseases. With each new threat, there has been a call for rapid vaccine development. Pathogens such as the Middle East Respiratory Syndrome coronavirus (MERS-CoV) and the Zika virus represent either new viral entities or viruses emergent in new geographic locales and characterized by novel complications. Both serve as paradigms for the global spread that can accompany new pathogens. In this paper, we review the epidemiology and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 143 publications
0
26
0
Order By: Relevance
“…GLS-5300 is the first MERS coronavirus vaccine to advance into human trials. Among vaccine candidates in development, 22 four have started or will soon start phase 1 testing, including measles-vectored, 9,23 chimpanzee adenovirus-vectored, 24 and modified vaccinia Ankaravectored vaccines, all expressing full-length S-glycoprotein. [25][26][27] DNA vaccines and viral-vectored vaccines use recombinant technology that allows for rapid vaccine design in response to emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…GLS-5300 is the first MERS coronavirus vaccine to advance into human trials. Among vaccine candidates in development, 22 four have started or will soon start phase 1 testing, including measles-vectored, 9,23 chimpanzee adenovirus-vectored, 24 and modified vaccinia Ankaravectored vaccines, all expressing full-length S-glycoprotein. [25][26][27] DNA vaccines and viral-vectored vaccines use recombinant technology that allows for rapid vaccine design in response to emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of the 2012 MERS‐CoV syndrome, despite some similarities with SARS‐CoV, the early mortality rate for the former achieved 60%, 10 remaining higher than 35% during the overall outbreak period, while for SARS‐CoV the mortality rate was about 10% 11 . A meta‐analysis suggested that MERS‐CoV infection was more likely to occur in patients with underlying cardiovascular diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Little may be known about the basic virology or immunology of a new pathogen, though the need for developing vaccines and therapeutics is urgent. 9 Some typical methods used as vaccine clinical assays are antibody-binding ELISAs, virus neutralization or bactericidal immunoassays, IFNγ-ELISpot or related cellular immune methodology using the target antigen or antigen-derived peptide pools, and detection of the pathogen through molecular or culture assays. Vaccine clinical assays measuring humoral and cellular immune responses developed early in a program will likely evolve as clinical development progresses or as the scientific knowledge base of the pathogen and relevant immunology broadens.…”
Section: Vaccine Clinical Assays Reference Reagents International Cmentioning
confidence: 99%
“…While the identification of an immune correlate of protection for each new vaccine is highly desirable, it is not always attainable. 3 Here we will use our recent experiences with the Middle East Respiratory Syndrome coronavirus (MERS-CoV) and Zika virus (ZIKV) [4][5][6][7][8][9] outbreaks and ensuing public health countermeasures for containment and vaccine development as examples of challenges faced during emerging infectious disease emergencies.…”
Section: Introductionmentioning
confidence: 99%